2021
DOI: 10.1186/s13229-021-00432-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomy and behavior in mice with a haploinsufficiency of AT-rich interactive domain 1B (ARID1B) throughout development

Abstract: Background One of the causal mechanisms underlying neurodevelopmental disorders (NDDs) is chromatin modification and the genes that regulate chromatin. AT-rich interactive domain 1B (ARID1B), a chromatin modifier, has been linked to autism spectrum disorder and to affect rare and inherited genetic variation in a broad set of NDDs. Methods A novel preclinical mouse model of Arid1b deficiency was created and validated to characterize and define neuro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 79 publications
2
31
0
Order By: Relevance
“…Therefore, we speculate that the dysregulation of neuroectoderm specification caused by ARID1B mutations may underlie both the cognitive impairment and craniofacial abnormalities that are typical of Coffin-Siris syndrome. This model is further supported by a significant overlap of differentially expressed genes identified in our study (neural crest formation) and in a recently published ARID1B-KO mouse model (brain tissue) 30 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, we speculate that the dysregulation of neuroectoderm specification caused by ARID1B mutations may underlie both the cognitive impairment and craniofacial abnormalities that are typical of Coffin-Siris syndrome. This model is further supported by a significant overlap of differentially expressed genes identified in our study (neural crest formation) and in a recently published ARID1B-KO mouse model (brain tissue) 30 .…”
Section: Discussionsupporting
confidence: 86%
“…Finally, we looked for potential overlap between our set of 2,356 differentially expressed genes at day 5 of iPSC differentiation toward CNCC and a set of genes identified as differentially expressed in a recent RNA-seq study which compared cerebellar tissue of ARID1B +/and ARID1B-wt mice 30 . Notably, 1,297 of the 2,356 genes (55%) found as differentially expressed in our study were also found as differentially expressed in the KO-mouse model dataset.…”
Section: Both the "Role Of Nanog In Mammalian Embryonic Stem Cell Pluripotency" And The "Pparα/rxrαmentioning
confidence: 99%
“…Susceptibility to primary generalized seizures was behaviorally assessed by systemically administering 80 mg/kg pentylenetetrazol (PTZ; a GABA A receptor antagonist) via intraperitoneal injection and observing the timing and progression of the subsequent convulsions following a protocol described previously [ 58 , 66 , 67 ]. Immediately following injection of PTZ, animals were individually placed in a clean empty standard mouse cage (27 cm l × 16.5 cm w × 12.5 cm h) and watched carefully by a trained observer blinded to genotype and treatment condition.…”
Section: Methodsmentioning
confidence: 99%
“…Pentylenetetrazol-induced seizures. Susceptibility to primary generalized seizures was behaviorally assessed by systemically administering 80 mg/kg pentelenetetrazol (PTZ; a GABA A receptor antagonist) via intraperitoneal injection and observing the timing and progression of the subsequent convulsions following a protocol described previously [55,63,64]. Immediately following injection of PTZ, animals were individually placed in a clean empty standard mouse cage (27 cm l x 16.5 cm w x 12.5 cm h) and watched carefully by a trained observer blinded to genotype and treatment condition.…”
Section: Beam Walkingmentioning
confidence: 99%